The Youth Knowledge Fair 2018 – Tracking Climate Change: Poster Presentation Guidelines and Logistics ... : Tracking Change: Local and Traditional Knowledge in Watershed Governance ... - Parlee, Brenda (University of Alberta Library, 2018)
The Youth Knowledge Fair 2018 – Tracking Climate Change brought together youth from the various jurisdictions of the Mackenzie River Basin including the Northwest Territories. The objectives of the knowledge fair were to: Create opportunities for high school youth (Grade 10-11) to connect with each other in Edmonton for three days of educational activities including knowledge sharing activities, educational workshops, keynote presentations from inspirational youth and Aboriginal leaders, tours of the University of Alberta; Support students to learn about their own histories, ecosystems and communities from elders and their communities and through their schools through submissions of poster projects; and, Encourage the development of research and written/oral communication skills by through a poster project related to the health of water, fish, fishing livelihoods and well-being of communities in the Mackenzie River Basin. The Knowledge Fair also created opportunities for youth and schools to network with ...